Cell-free nucleic acids in urine as potential biomarkers of kidney disease - Gyurászová, Marianna; Gaál Kovalčíková, Alexandra; Bábíčková, Janka; Hodosy, Július; Tóthová, Ľubomíra (Journal of Applied Biomedicine, 2018)
Kidney and uropoetic system diseases represent a major social, economic and health burden. This is mainly because early diagnosis of kidney dysfunction is currently unavailable, since the current markers are often reliably increased only after advanced progression of the renal diseases. Recently, circulating nucleosomes, DNA and numerous forms of RNA have been detected in human biological fluids, such as plasma, urine, saliva, and breast milk. Although their biological functions remain mostly unknown, they are attractive as potential biomarkers of various diseases. In urine, many of the circulating nucleic acids originate from the cells of the kidney and the urinary tract making these non-invasive and easily obtained new biomarkers in the nephrology or urology. This review focuses on cell free nucleic acids in urine and its potential in human studies. Although, there are some technical and biological limitations, the urinary circulating nucleic acids hold a great potential as new biomarkers of renal diseases.
Keywords: Neoplasms; nemoci ledvin; nádory; Deoxyribonuclease I; transrenální DNA; Cell-Free Nucleic Acids; Humans; postrenální DNA; deoxyribonukleasa I; lidé; Extracellular Vesicles; biologické markery; volné cirkulující nukleové kyseliny; extracelulární vezikuly; Biomarkers; DNA, Mitochondrial; mitochondriální DNA; Kidney Diseases